Lifetime Physical Activity and White Matter Hyperintensities in Cognitively-Intact Adults - Torres, Elisa R. (Nurs Res, 2019)
BACKGROUND: White matter hyperintensities (WMH) observed on magnetic resonance images are associated with depression and increase risk of stroke, dementia and death. The association between physical activity and WMH has been inconsistently reported in the literature, perhaps because studies did not account for a lifetime of physical activity or depression. OBJECTIVES: To determine the extent to which a lifetime of leisure-time physical activity is associated with less WMH while accounting for depression. METHODS: Face-to-face interviews were conducted with the Lifetime Total Physical Activity Questionnaire where the metabolic equivalent of task (MET) hours per week per year was calculated. Cognitively-intact participants also underwent magnetic resonance imaging where WMH as a percentage of intracranial volume (ICV) was obtained. Hierarchical multiple linear regression was performed to compare WMH in a more active group with no psychiatric history (n = 20, [Formula: see text] age = 62.2) with a less active group with no psychiatric history (n = 13, [Formula: see text] age = 64.0) and a less active group with history of late-onset depression (n = 14, [Formula: see text] age = 62.8). RESULTS: There was not a statistically significant difference in WMH (lg10) between the more and less active groups without a psychiatric history (b = .09, p > .05), or between the more active group without a psychiatric history and the less active group with a history of depression (b = .01, p > .05). The model was predictive of WMH (lg10), explaining an adjusted 15% of the variance in WMH (p = .041). DISCUSSION: A lifetime of leisure-time physical activity was not associated with WMH when accounting for depression.